The moral agency of civil society in post-election South Africa - Jacobus M. Vorster (In die Skriflig, 2024)
With the dawn of the new post-election Government of National Unity (GNU) in South Africa, this article ventures some ideas on the possible contribution of civil society to this new dispensation with the aim of turning the tide of moral decay and to set the course to hope and the development of a community of character. The research approaches the topic from a Reformed theological-ethical paradigm and considers social ethics within the context of the kingdom of God as the determinant of Christian social ethics. The study explores the possibility that the upcoming civil society could contribute to the much-needed moral ethos of South Africa by means of cooperation, confrontation, complimentary action, and co-option with respect to the state machinery in the GNU. The central theoretical argument of this research is that the incumbent civil society in South Africa – as one of the pillars of the constitutional democracy – can play an important role in the reinvention of a sound moral ethos as a moral agent over and against the GNU. To prove this hypothesis, the article discusses and submits the following areas of social involvement by civil society as proposals for further reflection: reviving morality, fostering moral leadership, being the voice of the poor, exposing corruption, shadowing public education, fighting crime, furthering constitutionalism, and promoting national dialogue.